The Effect of Baby Massage on Growth and Baby Development 0-12 Months at Mahanum Clinic - Desi Handayani Lubis; Yulia Safitri; Alfi Laili (PT Inovasi Pratama Internasional, 2022)
Several studies on baby massage provide reports related to the benefits of baby massage such as baby massage can increase body weight, increase growth, increase endurance, increase baby's concentration and make babies sleep more soundly, foster bonding attachment between parents and children and can improve mother's milk production. This type of research is pre-experimental with one group pretest-posttest design. The study population was infants aged 0 -12 months. The research sample was 28 infants aged 0-12 months. The research instrument used a questionnaire. Wilcoxon test statistical test data processing.The results showed that the growth and development of infants aged 0-12 months before being given baby massage was known to 28 respondents, the results showed that the growth and development of infants in the rising category before the baby massage was carried out were 5 respondents (17.9%) and the growth and development of infants in the fixed category. before the baby massage was carried out as many as 23 respondents (82.1%) and the growth and development of babies in the rising category after the baby massage was 26 respondents (92.9%) and Growth and Development in the fixed category before the baby massage was 2 respondents (7, 1%). Wilcoxon statistical test showed that the significant value of p-value = 0.000 <α (0.05), so that H was accepted.The conclusion of the study means that there is an effect of baby massage on the growth and development of infants aged 0-12 months at Mahanum Clinic, Medan.